Blockade of TGF-β 1 Signalling Inhibits Cardiac NADPH Oxidase Overactivity in Hypertensive Rats. (3rd June 2012) - Miguel-Carrasco, José Luis; Baltanás, Ana; Cebrián, Carolina; Moreno, María U.; López, Begoña; Hermida, Nerea; González, Arantxa; Dotor, Javier; Borrás-Cuesta, Francisco; Díez, Javier; Fortuño, Ana; Zalba, Guillermo
Abstract : NADPH oxidases constitute a major source of superoxide anion (⋅ O 2   - ) in hypertension. Several studies suggest an important role of NADPH oxidases in different effects mediated by TGF-β 1. In this study we show that chronic administration of P144, a peptide synthesized from type III TGF-β 1 receptor, significantly reduced the cardiac NADPH oxidase expression and activity as well as in the nitrotyrosine levels observed in control spontaneously hypertensive rats (V-SHR) to levels similar to control normotensive Wistar Kyoto rats. In addition, P144 was also able to reduce the significant increases in the expression of collagen type I protein and mRNA observed in hearts from V-SHR. In addition, positive correlations between collagen expression, NADPH oxidase activity, and nitrotyrosine levels were found in all animals. Finally, TGF-β 1-stimulated Rat-2 exhibited significant increases in NADPH oxidase activity that was inhibited in the presence of P144. It could be concluded that the blockade of TGF-β 1 with P144 inhibited cardiac NADPH oxidase in SHR, thus adding new data to elucidate the involvement of this enzyme in the profibrotic actions of TGF-β 1.